Biomarkers and coronary lesions predict outcomes after revascularization in Non-ST-Elevation Acute Coronary Syndrome - Lindholm, Daniel; Giannitsis, Evangelos (Clinical chemistry, 2017)
BACKGROUND: Risk stratification in non-ST-elevation acute coronary syndrome (NSTE-ACS) is currently mainly based on clinical characteristics. With routine invasive management, angiography findings and biomarkers are available and may improve prognostication. We aimed to assess if adding biomarkers [high-sensitivity cardiac troponin T (cTnT-hs), N-terminal probrain-type natriuretic peptide (NT-proBNP), growth differentiation factor 15 (GDF-15)] and extent of coronary artery disease (CAD) might improve prognostication in revascularized patients with NSTE-ACS. METHODS: In the PLATO (Platelet Inhibition and Patient Outcomes) trial, 5174 NSTE-ACS patients underwent initial angiography and revascularization and had cTnT-hs, NT-proBNP, and GDF-15 measured. Cox models were developed adding extent of CAD and biomarker levels to established clinical risk variables for the composite of cardiovascular death (CVD)/spontaneous myocardial infarction (MI), and CVD alone. Models were compared using c-statistic and net reclassification improvement (NRI). RESULTS: For the composite end point and CVD, prognostication improved when adding extent of CAD, NT-proBNP, and GDF-15 to clinical variables (c-statistic 0.685 and 0.805, respectively, for full model vs 0.649 and 0.760 for clinical model). cTnT-hs did not contribute to prognostication. In the full model (clinical variables, extent of CAD, all biomarkers), hazard ratios (95% CI) per standard deviation increase were for cTnT-hs 0.93(0.81-1.05), NT-proBNP 1.32(1.13-1.53), GDF-15 1.20(1.07-1.36) for the composite end point, driven by prediction of CVD by NT-proBNP and GDF-15. For spontaneous MI, there was an association with NT-proBNP or GDF-15, but not with cTnT-hs. CONCLUSIONS: In revascularized patients with NSTE-ACS, the extent of CAD and concentrations of NT-proBNP and GDF-15 independently improve prognostication of CVD/spontaneous MI and CVD alone. This information may be useful for selection of patients who might benefit from more intense and/or prolonged antithrombotic treatment. ClinicalTrials.gov Identifier: NCT00391872